Penggunaan Kalimat dalam Teks Eksposisi Karya Siswa Kelas X SMA Negeri 1 Nan Sabaris Kabupaten Padang Pariaman - Sari, Intan Juwita; Hafrison, Mohd. (ALSYS, 2023)
This study aims to describe the use of sentences in exposition texts in terms of structural clarity, logical meaning, frugality of words and standardization of words in exposition texts by class X students of SMA Negeri 1 Nan Sabaris, Padang Pariaman Regency. This type of research is qualitative research using descriptive methods. The data to be obtained are words and sentences obtained from research data sources. The source of the data used in this study was exposition texts by class X students of SMA Negeri 1 Nan Sabaris, Padang Pariaman Regency, for the 2021/2022 academic year with a total of 30 student exposition texts. The data collection technique in this study is the fishing technique. The instrument in this study was the researcher himself and assisted by an inventory table. Based on the results of the study, it can be concluded that First, in terms of structural clarity consisting of clarity of active and passive structures, 47 non-standard sentences were found, 18 non-standard adverbial subjects were found, five non-standard predicates were found, non-subject adverbs were found. five non-standard sentences, and the subject is not missing found 16 non-standard sentences. Second, in terms of logical meaning, it consists of a logical relationship between the meanings of S and P found in 16 non-standard sentences and a logical relationship of detailed (parallel) meanings found in 13 non-standard sentences. Third, from the point of view of saving words consisting of using one subject from the same subject, three non-standard sentences were found, using one word from several synonymous words, 90 non-standard sentences were found, and using the words needed to express the author's intent, 125 non-standard sentences were found. . Fourth, in terms of word standardity, 32 non-standard words were found. the results obtained prove that the use of sentences in expository texts for class X students of SMA Negeri 1 Nan Sabaris Padang Pariaman Regency is still low.